Application of Novel Flotation Process for Removal of Feldsphatic Minerals from Quartz Sands - Kursun, Ilgin; G. Ozkan, Safak; Cinku, Kenan; Faruk Eskibalci, M. (Asian Journal of Chemistry, 2016)
In this study, conventional flotation process using hydrofluoric acid was compared to a novel flotation process without using hydrofluoric acid for separation of feldspar from quartz sands. In the new method, feldspars are floated from quartz sands using two different reagents; sodium oleate and dodecyl amine acetate together as collectors for satisfactory and environment friendly beneficiation without using hydrofluoric acid.